THE IMPLEMENTATION OF INCLUSIVE LEARNING DESIGN AT AL AZHAAR TULUNGAGUNG ISLAMIC ELEMENTARY SCHOOL IN THE 5.0 ERA - Erfiana, Nita Agustina Nurlaila Eka; Mufidati, Khusnul; Pusvitasari, Rita (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
A phenomenon in society shows that normal children and children with disabilities cannot be separated as social communities. Inclusive education programs are designed to be implemented in schools to help children with disabilities receive an education alongside their peers and reach their full potential. This research aims to examine the implementation of inclusive learning design in the 5.0 era. Inclusive learning designs must be prepared and implemented with mature concepts based on students' goals, needs, and abilities. This research uses a qualitative descriptive approach with Al Azhaar Islamic Elementary School (IES) Tulungagung, Tumur Java, Indonesia as the research location. Data collection instruments in this research are observation, interviews, and documentation. The informants involved in this research were 40 people consisting of students, teachers, and inclusive school managers at Al-Azhaar Islamic Elementary School, Tulungagung, who were selected using purposive sampling techniques. Inductive data analysis was carried out in this research with stages of data reduction, data presentation, and drawing conclusions or verification. The results of this research show the characteristics of inclusive learning that is friendly and comfortable for students with special needs. The design and development of inclusive learning is carried out by ensuring that life skills and technology learning are maintained and mastered by students as a scientific preparation for the future.